An Empirical Investigation of Website Design Characteristics, Consumer Trust, and Intention to Shop Online in Hyderabad - Ahamad, Mohd Layaq; Zafar, Shaikh Mohd (Indian Journal of Marketing, 2013)
The main purpose of the present study is to examine the effect of Website design characteristics and Consumer Trust factors influencing consumers' Intention to shop online with reference to online shopping in Hyderabad. The population of this research consisted of online shoppers from Hyderabad. The sample for the study comprised of 200 online shoppers. Respondents belonged to different age groups and occupations having prior experience in online shopping. A pre-structured questionnaire was used with a 5 point Likert rating scale to measure the factors influencing the respondents' intention to shop online. Snowball sampling was used to collect the data from the sample respondents. Statistical techniques such as mean, standard deviation, correlation, and multiple regression were used for data analysis. The empirical results revealed that Website Design characteristics and Consumer Trust have a strong and positive influence on Consumers' Intention to Shop Online. The study suggests, among other things, that companies must focus on improving their website design characteristics to develop consumers' trust towards online shopping.